Lama guanicoe remains from the Chaco ecoregion (Córdoba, Argentina) : an osteological approach to the characterization of a relict wild population - Costa, Thiago; Barri, Fernando (2021)
Fil: Costa, Thiago. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Museo de Antropología. Instituto de Antropología de Córdoba; Argentina.